Endoscopic management of sinonasal hemangiopericytoma: case report and literature review - Francisco Ferreira Rosa; José Gameiro Santos; Jorge Oliveira; Cecília Almeida Sousa (Case Reports)
Introduction: Hemangiopericytoma is a rare vascular tumor of the sinonasal region, associated with epistaxis and nasal obstruction as the main symptoms. When located in this region, it has special clinical characteristics that differentiate it from others.